2001
DOI: 10.1186/1471-2350-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Change of dopamine receptor mRNA expression in lymphocyte of schizophrenic patients

Abstract: BackgroundThough the dysfunction of central dopaminergic system has been proposed, the etiology or pathogenesis of schizophrenia is still uncertain partly due to limited accessibility to dopamine receptor. The purpose of this study was to define whether or not the easily accessible dopamine receptors of peripheral lymphocytes can be the peripheral markers of schizophrenia.Results44 drug-medicated schizophrenics for more than 3 years, 28 drug-free schizophrenics for more than 3 months, 15 drug-naïve schizophren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
2
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 24 publications
(25 reference statements)
4
72
2
3
Order By: Relevance
“…The extent of dopamine receptor expression is different among diseases (51)(52)(53)(54)(55). For example, expression of D3 receptor is upregulated in schizophrenia (51,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of dopamine receptor expression is different among diseases (51)(52)(53)(54)(55). For example, expression of D3 receptor is upregulated in schizophrenia (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…For example, expression of D3 receptor is upregulated in schizophrenia (51,52). Expression of D2-like-R decreased in Alzheimer's disease (53).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, significant decreasing in D2-D4 were reported in PBMCs of non-small cell long cancer (Shaikhpoor et al, 2012). Kwak et al (2001) were reported significant elevation in the expression level of D2 and D3 genes in schizophrenia (Kwak et al, 2001). In arthritis rheumatoid, the expression of D2 was decreased and D4 was elevated, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There are five different subtypes for dopamine receptors (DRD1-DRD5) which are classified into two families including D1-like family (stimulatory receptors) and D2-like family (inhibitory receptors) (Kirillova et al, 2008;Beaulieu and Gainetdinov, 2011). Prior studies reported that in different diseases the gene expression of dopamine receptors have been altered in immune and nervous systems (Kwak et al, 2001;Jafari et al, 2013). For instance, significant decreasing in D2-D4 were reported in PBMCs of non-small cell long cancer (Shaikhpoor et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation